METHODOLOGICAL MODEL FOR DEVELOPING CRITICAL THINKING OF OLDER EDUCATORS IN PRESCHOOL EDUCATION (American Journal of Pedagogical and Educational Research, 2024)
This article talks about the methodical model of developing critical thinking of older students in preschool education.